Long Way Home - Austin, Lynn (Tyndale House Publishers, 2022)
Peggy Serrano couldn't wait for her best friend to come home from the war. But the Jimmy Barnett who returns is much different from the Jimmy who left, changed so drastically by his experience that he can barely function. When he attempts the unthinkable and his parents check him into the VA hospital, Peggy determines to help the Barnetts unravel what might have happened to send their son over the edge, starting by contacting Jimmy's war buddies and trying to identify the mysterious woman in the photo they find in Jimmy's belongings. Seven years earlier, sensing the rising tide against her people, Gisela Wolff and her family flee Germany aboard the passenger ship St. Louis, bound for Havana, Cuba. Gisela meets Sam Shapiro, the love of her life, on board, but the ship is eventually denied safe harbor and sent back to Europe. This begins Gisela's perilous journey of exile and survival, made possible only by the kindness and courage of a series of strangers she meets along the way, including one man who will change the course of her life
Description based on publisher supplied metadata and other sources
Keywords: Young women; Life change events; Post-traumatic stress disorder; Friendship; Refugees; World War; 1939-1945; Man-woman relationships; Survival; Electronic books; Jeunes femmes - New York (État) - Hudson - Romans; nouvelles; etc; Événements stressants de la vie - Romans; nouvelles; etc; État de stress post-traumatique - Romans; nouvelles; etc; Amitié - Romans; nouvelles; etc; Réfugiés - Europe - Romans; nouvelles; etc; Guerre mondiale; 1939-1945 - Juifs - Sauvetage - Allemagne - Romans; nouvelles; etc; Relations entre hommes et femmes - Romans; nouvelles; etc; Habiletés de survie - Romans; nouvelles; etc; FICTION / Christian / Historical; FICTION / Romance / Historical / 20th Century; FICTION / Historical / World War II; World War; 1939-1945 - Fiction; Christian life - Fiction; Christian fiction; Fiction; Historical fiction; Romans chrétiens